2019
DOI: 10.7556/jaoa.2019.007
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Aberrations of the Auditory Brainstem in Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental condition associated with difficulties in the social, communicative, and behavioral domains. Most cases of ASD arise from an unknown etiologic process, but there are numerous risk factors, including comorbidities and maternal exposures. Although it is not part of the diagnostic criteria, hearing difficulties ranging from deafness to hyperacusis are present in the majority of persons with ASD. High-functioning children with ASD have been found to have signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 85 publications
(85 reference statements)
1
13
0
1
Order By: Relevance
“…A number of proposed causes of hyperacusis have been introduced, but it is important to consider that correlates of hyperacusis may differ across individual cases of ASD and hyperacusis given the extreme level of variability in the makeup of the brain depending on the level of severity of the ASD. Smith, Storti, Lukose, and Kulesza [ 34 ] reported imaging studies that demonstrated cerebellar and brainstem hypoplasia in the ASD population compared to age matched people with neurotypical development, including hypoplasia of the facial nucleus and superior olivary complex. Another interesting study highlighting anatomical causes of hyperacusis in the ASD population noted that 29% of autistic people and hyperacusis were found to have superior semicircular canal dehiscence as demonstrated by computerized tomography imaging [ 35 ].…”
Section: Hyperacusis and Asdmentioning
confidence: 99%
“…A number of proposed causes of hyperacusis have been introduced, but it is important to consider that correlates of hyperacusis may differ across individual cases of ASD and hyperacusis given the extreme level of variability in the makeup of the brain depending on the level of severity of the ASD. Smith, Storti, Lukose, and Kulesza [ 34 ] reported imaging studies that demonstrated cerebellar and brainstem hypoplasia in the ASD population compared to age matched people with neurotypical development, including hypoplasia of the facial nucleus and superior olivary complex. Another interesting study highlighting anatomical causes of hyperacusis in the ASD population noted that 29% of autistic people and hyperacusis were found to have superior semicircular canal dehiscence as demonstrated by computerized tomography imaging [ 35 ].…”
Section: Hyperacusis and Asdmentioning
confidence: 99%
“…There are multiple brainstem nuclei critical for the processing of auditory information including the cochlear nuclei, the nucleus of the trapezoid body, superior olivary complex, nuclei of the lateral lemniscus, and the inferior colliculus (schematic in Figure 7 ; Pickles, 2015 ; Smith et al, 2019 ). There are electrophysiological data (measurement of ABR, auditory brainstem response) suggesting that the brainstem structures may be affected in ASD ( Rosenhall et al, 1988 ; Kwon et al, 2007 ).…”
Section: What Do We Know About the Brain In Asd: Candidate Structures And Their Connectionsmentioning
confidence: 99%
“…Sensory processing deficits, specifically of auditory and vestibular information, are also characteristic of ASD (discussion and additional references in Baranek et al, 2006 ; Lane et al, 2010 ; Mansour and Kulesza, 2020 ). While peripheral hearing loss is not found ( Beers et al, 2014 ), there are many studies showing auditory dysfunction in children with ASD (references in Rimland and Edelson, 1995 ; Lukose et al, 2013 ; Kozou et al, 2018 ; Smith et al, 2019 ). Lukose et al (2013) studied the acoustic stapedial reflex (ASR: contraction of the stapedius muscle of the middle ear in response to loud sounds) and found lower thresholds and longer latencies in ASD subjects.…”
Section: Introductionmentioning
confidence: 99%
“… Fitzpatrick et al (2014) found that approximately 29.4% of children with ASD had profound hearing loss and that those children with hearing loss benefited from the use of hearing aids. In addition, hearing dysfunction was attributed to ASD-related neuronal degeneration of the auditory pathway ( Smith et al, 2019 ). In contrast, Szymanski et al (2012) found a high prevalence of ASD among children with hearing loss, supporting that peripheral auditory dysfunction may be associate with functional impairment in ASD ( Demopoulos and Lewine, 2016 ).…”
Section: Autism Spectrum Disordermentioning
confidence: 99%